Technological advances in out-of-hospital care: Digital solutions, Asia Pacific experiences, and inherent challenges - Li Zhang; Zeqi Liu; Kai Mo; Wenting Pu; Jiali Yin; Ziyu Ma; Zhuocheng Jiang; You Wu (Informatics and Health)
The healthcare systems in the Asia-Pacific region are confronted with immense challenges due to an aging population and its rising demand for medical services. Out-of-hospital care supported by digital medical technology has emerged as a potential solution. Countries in the Asia-Pacific region are actively exploring the use of innovative digital technologies to develop out-of-hospital care programs tailored to each nation's context. However, there are also many non-technical challenges like technology maturity, qualification of healthcare staff, incentives of physicians within hospitals, funding and reimbursement, which inhibit the adoption of out-of-hospital. This review examines the current state of out-of-hospital care in four countries in the Asia-Pacific region: the United States, Australia, Singapore, and China. It proposes a practical technical catalog of out-of-hospital care, analyzes existing development challenges, and offers recommendations based on international best practices. Moving forward, it’s urgent to further integrate technologies and the health system, and navigate multi-stakeholder collaboration in out-of-hospital care.